m6A demethylase ALKBH5 drives denervation‐induced muscle atrophy by targeting HDAC4 to activate FoxO3 signalling - Yuantong Liu; Tianjian Zhou; Qinghe Wang; Runhan Fu; Zengfu Zhang; Nandi Chen; Zhizhong Li; Guoyong Gao; Songlin Peng; Dazhi Yang (Wiley, 2022)
Abstract Background Skeletal muscle atrophy is a common clinical manifestation of various neurotrauma and neurological diseases. In addition to the treatment of primary neuropathies, it is a clinical condition that should be investigated. FoxO3 activation is an indispensable mechanism in denervation‐induced muscle atrophy; however, upstream factors that control FoxO3 expression and activity have not been fully elucidated. N6‐methyladenosine (m6A) methylation is a novel mode of epitranscriptional gene regulation that affects several cellular processes. However, the biological significance of m6A modification in FoxO3‐dependent atrophy is unknown. Methods We performed gain‐of‐function and loss‐of‐function experiments and used denervation‐induced muscle atrophy mouse model to evaluate the effects of m6A modification on muscle mass control and FoxO3 activation. m6A‐sequencing and mass spectrometry analyses were used to establish whether histone deacetylase 4 (HDAC4) is a mediator of m6A demethylase ALKBH5 regulation of FoxO3. A series of cellular and molecular biological experiments (western blot, immunoprecipitation, half‐life assay, m6A‐MeRIP‐qPCR, and luciferase reporter assays among others) were performed to investigate regulatory relationships among ALKBH5, HDAC4, and FoxO3. Results In skeletal muscles, denervation was associated with a 20.7-31.9% decrease in m6A levels (P < 0.01) and a 35.6-115.2% increase in demethylase ALKBH5 protein levels (P < 0.05). Overexpressed ALKBH5 reduced m6A levels, activated FoxO3 signalling, and induced excess loss in muscle wet weight (−10.3% for innervation and −11.4% for denervation, P < 0.05) as well as a decrease in myofibre cross‐sectional areas (−35.8% for innervation and −33.3% for denervation, P < 0.05) during innervation and denervation. Specific deletion of Alkbh5 in the skeletal muscles prevented FoxO3 activation and protected mice from denervation‐induced muscle atrophy, as evidenced by increased muscle mass (+16.0%, P < 0.05), size (+50.0%, P < 0.05) and MyHC expression (+32.6%, P < 0.05). Mechanistically, HDAC4 was established to be a crucial central mediator for ALKBH5 in enhancing FoxO3 signalling in denervated muscles. ALKBH5 demethylates and stabilizes Hdac4 mRNA. HDAC4 interacts with and deacetylates FoxO3, resulting in a significant increase in FoxO3 expression (+61.3-82.5%, P < 0.01) and activity (+51.6-122.0%, P < 0.001). Conclusions Our findings elucidate on the roles and mechanisms of ALKBH5‐mediated m6A demethylation in the control of muscle mass during denervation and activation of FoxO3 signalling by targeting HDAC4. These results suggest that ALKBH5 is a potential therapeutic target for neurogenic muscle atrophy.